A GAME-BASED ACTIVITY TO DETECT IMPAIRED EMOTION RECOGNITION FOR POST STROKE PATIENTS - NASIR, ILYA KHALIJAH (IRC, 2020)
Stroke can happen to anyone and anywhere. Stroke occurs when there is an interruption of blood supply to the brain. There are a lot of side effects due to stroke. One of the side effects is deficiency of facial emotion recognition skills of one individual. Deficiency of facial emotion recognition also called as Impaired facial emotion recognition. Impaired facial emotion recognition can happen to patient who just recovered from stroke. Impaired facial emotion recognition occurs when one individual has difficulty on recognizing other people’s emotions. This paper will introduce a new implementation of existing Virtual Reality technology that aims to help for early detection of impaired emotion recognition skills of post-stroke patients. This research needs to study the effect of existing facial recognition tests into the Virtual Reality game-based activity. To conduct the preliminary studies, research on literature review of related topics and study on the existing technology has been done. For the system development, Agile Methodology has been applied for the System Development Life Cycle (SDLC) technique. This virtual reality game-based activity that will be developed will has a great potential to help the post stroke patients to adapt with their post stroke lives since the deficiency can be detected early. Early detection of this deficiency can help them to get the treatment provided by the clinicians.